Enhancing quality engineering education through mobile learning integration: a contribution to SDG 4 - M. Ramli, Roshahliza; Pebrianti, Dwi; Najib, Muhammad Sharfi (Editora Alumni In, 2025)
Introduction: Integrating mobile learning in engineering education enhances accessibility, supporting Sustainable Development Goal (SDG) 4 for inclusive and quality education. Mobile apps linked to learning systems overcome geographical and socioeconomic barriers, enabling underserved populations to learn. By leveraging smartphones and interactive content, educators foster inclusivity and equip students with essential digital literacy for a technology driven workforce. Objective: The objective of this study is to investigate the effectiveness of mobile learning method in engineering and technical courses, with the aim of better results in student learning experience and academic performance. Method: This research implemented personalized online activities via a Moodle mobile application in two engineering courses. The key elements included additional video lectures, practice questions with immediate feedback, and self-assessment quizzes, all emphasizing self directed learning. The effect on student performance and perceptions was assessed through grade analysis and end-of-course surveys. Results and Discussion: The implementation resulted in significant enhancements in student achievement and course learning outcomes. The percentage of students achieving higher grades rose by 15-30% between course offerings, with particularly substantial gains at the A grade level. The achievement of specific learning outcomes improved by 13-26%. Surveys revealed robust participation in mobile app-enabled activities and increased motivation throughout the semester. Research Implications: The practical and theoretical implications of this research are discussed, providing insights into how the results can be applied or influence practices in the field of engineering and technical education. Originality/Value: This study contributes to the literature by highlight the potential of mobile learning to boost student success in engineering courses by providing accessible, engaging content. This research offers guidance on best practices for learning management system design to maximize the benefits of mobile technology for the evolving paradigms of engineering and technical education.